Evaluating the Total Active Power Loss under Different Placement of Photovoltaic Power Plants Using an Effective Northern Goshawk Optimization - Dao Trong Tran; Bach Hoang Dinh (Journal of Technical Education Science, 2024)
This research presents a detailed evaluation of the total active power loss (TAPL) under different placements of photovoltaic power plants (PVPs) in the electric distribution network (EDN) IEEE 33-node. Three study cases have been conducted to serve the initial intention, including 1) optimizing both rated power and position of a PVP on selected EDN; 2) optimizing the positions of different quantities of PVPs independently to the grid with the same rated power, and 3) optimizing a sole PVP with a wide range of rated power. In all three study cases, northern goshawk optimization (NGO) is the primary search method for determining the essential results and data, especially in the last two cases, after proving its competitive performance in the first case compared to other methods. The results in study cases 2 and 3 indicated that for reaching the minimum value of TAPL, placing many PVPs independently on the grid simultaneously is the best implementation. Notably, the placement 7 PVPs with a total rated power of 2800kW has resulted in a significantly better TAPL than all the results in study case 3. However, for the situation where EDN can only adopt a sole PVP, all the data and results presented in study case 3 are also good academic material.